2014
DOI: 10.9708/jksci.2014.19.5.119
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Digital Storytelling Based Programming Education

Abstract: This study conducted digital storytelling-based programing education targeting students at elementary school and analyzed educational significance as looking into perception on programing, making cognitive-affective assessments and having interviews. The results of the study are provided as follows. First, in terms of ex-post perception, from all the areas of fun, usefulness and ease of use, statistically significant differences were observed. It was also learned that female students have positive perception s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Csizmar Dalal () reported that many creative skills such as researching, gathering information, organizing information, creating new ideas, designing, writing, expressing themselves, putting out products, and solving problems are being supported by digital storytelling activities. Therefore, the finding that programming activities will be effective with digital story activities (Park, ) coincides with the findings obtained in this study.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Csizmar Dalal () reported that many creative skills such as researching, gathering information, organizing information, creating new ideas, designing, writing, expressing themselves, putting out products, and solving problems are being supported by digital storytelling activities. Therefore, the finding that programming activities will be effective with digital story activities (Park, ) coincides with the findings obtained in this study.…”
Section: Resultssupporting
confidence: 90%
“…It also supports many creative skills that are tried to contribute to students such as research, collecting and organizing information, creating new ideas, designing, writing, expressing themselves, putting out products, solving problems are supported in programming teaching (Csizmar Dalal, ; Dupain & Maguire, ; Hathorn, ; Sarıca & Usluel, ; Yang & Wu, ). At this point, it can be predicted that digital storytelling will increase the programming achievement (Park, ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%